Finding God Alongside Trials: Catholicism and Resilience Among Queer Filipino Emerging Adults - Chongbian, Sabine F. (Archīum Ateneo, 2021)
In the Philippines, queer individuals face adversities related to their sexual orientation and gender identity and expression (SOGIE), with the country’s strong Catholicism perceived as a source of adversity for these individuals. Despite this, studies have found religious involvement and a religious community in certain contexts can be used to strengthen queer individuals’ resilience, allowing them to overcome these adversities. The present study investigated queer Catholic emerging adults’ experiences of resilience through faith in a Southeast Asian context. Queer Filipino Catholic emerging adults aged between 18 and 25 were interviewed, and their life experiences explored using the narrative approach. Results show and validate queer emerging adults go through various forms of adversities, many of which are related to the religious culture in the country. A hypothesized framework culled from the data depicts how participants were able to overcome these adversities by engaging with a supportive Catholic community, renewing their understanding of faith teachings, and having a sense of providence. A major contribution of the paper is how collectivist behaviors and social responsibility resulting in building communities of resilience can be beneficial in progressing individual queer resilience within the bounds of faith and sexuality. (PsycInfo Database Record (c) 2021 APA, all rights reserved)